ENHANCING AWARENESS OF AUTISM SPECTRUM DISORDER AMONG UNIVERSITY STUDENTS - Usman Jaffer; Ajwa Raudha Shamsool; Athila Aisyah Mohd Jamberos; Jamaliah Jaafar; Muhammad Faris Jafri; Munirah Izyan Mohd Nor Hairi; Nur Syafiqah Shuzarina Mohammad Zakaria; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Autism Spectrum Disorder (ASD) is a developmental condition that affects social interaction, communication, and behaviour, often resulting in social stigmatization and employment barriers. This study aimed to examine the effectiveness of a targeted awareness campaign in increasing knowledge and fostering positive attitudes toward ASD among undergraduates at the International Islamic University Malaysia (IIUM). A mixed-methods approach was employed. Qualitatively, semi-structured interviews with staff at Akademi Remaja Islam Autisma (ARISMA) provided localized insights into the challenges experienced by young adults with ASD. Quantitatively, 50 undergraduate students completed a pre-test and post-test questionnaire adapted from Alsehemi et al. (2017). Paired-sample t-test results indicated a significant increase in the participants’ knowledge and awareness of ASD after engaging with the campaign, demonstrated by a rise in mean scores from 26.02 to 30.42 (p < .05). Qualitative feedback indicated that the campaign’s digital infographics effectively disseminated information on ASD, but participants suggested more interactive, in-person events for broader impact. The findings corroborate the importance of targeted awareness and education programs in reducing stigma and promoting inclusion for individuals with ASD. Future recommendations include expanding the sample size, refining campaign materials for greater accessibility, and implementing longitudinal evaluations to assess sustained changes in knowledge, attitudes, and practices.